CULTURAL CENTER KABUPATEN LANDAK - Dasilelo, Alef Experancio Ximenes; Kalsum, Emilya; Br. Gultom, Bontor Jumaylinda (JMARS: Jurnal Mosaik Arsitektur, 2021)
Landak Regency is one of the areas in West Kalimantan that is rich in cultural heritage. Various forms of cultural heritage come from 2 large ethntic, it is Dayak and Malay ethnic. Nevertheless, all the wealth and cultural heritage has not been integrated and has a special container. From the potential and problems, it is necessary to hold a container that can shelter and accommodate all components of cultural activities in the landak regency. This refers to the Cultural Center of Landak Regency. The design method used in the design of the Cultural Center is a seven-step design method, which starts from the search for ideas, data collection, data processing, data analysis, determining concepts and deciding the design results. This method refers to an area-scale Cultural Center design whose all variants of activities will be sheltered by the composition of several building times implemented based on their functions and activities, this Cultural Center will be supported by the application of a sheath system that will be implemented through the typical patterns of culture of Landak Regency with the emphasis of the concept more to modern minimalist buildings but rich in cultural value.